Sociodemographic and behavioral aspects associated with positive self-perceived health among high school teenagers - Bispo de Almeida, Claudio; Andrade Rios, Marcela; de Almeida Gomes, Marcius; Vinicius Nahas, Markus (O Mundo da Saúde, 2020)
Self-perceived health is considered to be a predictor of mortality and morbidity as it encompasses a global health assessment based on an analysis of the sociodemographic and behavioral aspects associated with positive self-perceived health among high school adolescents. This study aimed to identify the factors regarding sociodemographic aspects and health behaviors associated with positive self-perceived health of teenage students in the city of Guanambi, BA. Therefore, a cross-sectional epidemiological study was carried out with 1,140 adolescents aged between 15 and 19 years old enrolled in public and private schools in the city, using a questionnaire. Data analysis was carried out by means of binary logistic regression, with variables that presented p<20% remaining in the final model, and p<0.05 was considered statistically significant. Among the respondents, 60.9% were female, 69.3% were aged 15 to 17 years old, and 68.6% came from families with a monthly income of up to two minimum wages. It was observed that 78.3% of students rated their health positively (those who reported an excellent or good self-perceived health). In general, this outcome was associated with younger (p=0.02) males (p<0.01), with experience using drugs (p=0.04), who were physically activity (p=0.02), and had a lower stress level (p<0.01). In boys, self-perceived health was associated with physical activity (p=0.04) and lower levels of stress (p<0.01). In the analysis with the girls, the outcome was associated with the age group (p<0.01) and with lower levels of stress (p<0.01). It was concluded that the prevalence of positive selfperceived health among high school adolescents was different for males and females, as well as their associated factors.